LA RESPONSABILIDAD SOCIAL VERSUS EL EMPRENDIMIENTO EN ADMINISTRACIÓN DE EMPRESAS Y CONTADURÍA DE LA UNIVERSIDAD DE CUNDINAMARCA, SEDE FUSAGASUGÁ (2016)
This document refers to applied research in the University of Cundinamarca and aims to establish the importance that magazine social responsibility in entrepreneurship as vocation and leadership of students last semester in business administration and accounting, however that in both programs the theme of entrepreneurship is a transverse line from the profile defined for graduates of these undergraduate.As theoretical reference, has been supported by authors such as Allen K & al., Shumpetier, Drucker, Shane &Collins among others. In the same way it based on the project educational institutional of the University of Cundinamarca, the Faculty of Administrative Sciences, economic and accounting education project; the law 1014 2006, among others.